Effect of heterocycles on field-effect transistor performances of donor-acceptor-donor type small molecules - Chini, Mrinmoy Kumar; Mahale, Rajashree Y.; Chatterjee, Shyambo (Chemical Physics Letters, 2016)
Two D-A-D small molecules comprising triphenylamine and diketopyrrolopyrrole were synthesized having either furan or thiophene connected to the fused lactam ring. In this design, furan/thiophene diketopyrrolopyrrole acts as an acceptor and triphenylamine acts as a donor. Propeller shaped triphenylamine has its effect on packing, processability and plays a vital role in determining the pi-pi molecular orbital stacking in such compounds and thus the mobility of charge carriers. With TDPPT and FDPPT, maximum hole carrier mobility obtained is 2.88 x 10(-3) cm(2) V-1 s(-1) and 1.60 x 10(-3) cm(2) V-1 s(-1), respectively using bottom gate bottom contact field-effect transistor. (C) 2016 Elsevier B.V. All rights reserved.

F and CF3 substituted solution processable oligo para-phenylenevinylene for ambipolar and hole-transporting organic field effect transistors - Chini, Mrinmoy Kumar; Das, Chayanika; Chatterjee, Shyambo (Chemical Physics Letters, 2016)
We have synthesized benzotrifluoromethyl group substituted para-phenylenevinylene oligomer (denoted as PI) and a cooligomer (denoted as PII) by Gilch polymerization route. The ambipolar field-effect transistor (FET) material PI shows hole and electron mobility 1 x 10 (4) cm(2) V (1) s (1) and 2 x 10 (5) cm(2) V (1) s (1) respectively. PII shows only hole mobility as high as 0.05 cm(2) V (1) s (1) as p-type material. This work highlights the progress of hole-transporting as well as ambipolar material for para-phenylenevinylene derivatives. The results are enlightened on the basis of presence of electronegative substituents and structural modification of the oligomer backbone. (C) 2016 Elsevier B.V. All rights reserved.

Effect of side-chain functionality on the organic field-effect transistor performance of oligo(p-phenylenevinylene) derivatives - Chini, Mrinmoy Kumar; Chatterjee, Shyambo (Journal of Applied Polymer Science, 2017)
In order to observe the effects of the substitution of electronegative flourine with aromatic groups in oligo(p-phenylenevinylene) compounds on their packing, morphology, and charge carrier mobility, we have synthesized napthol-substituted oligo(p-phenylenevinylene) compounds and examined their solubility, redox properties, thin film morphologies, and charge carrier properties. To date, very few examples of conjugated oligomers bearing napthol side groups have been reported in the literature. After annealing at 150 degrees C, the mobility of S1, S2, and S3 was 4.0x10(-2) cm(2) V-1 s(-1), 1.2x10(-2) cm(2) V-1 s(-1), and 2.6x10(-3) cm(2) V-1 s(-1), respectively. (c) 2017 Wiley Periodicals, Inc.

Hydrothermally reduced nano porous graphene–polyaniline nanofiber composites for supercapacitor - Chini, Mrinmoy Kumar; Chatterjee, Shyambo (FlatChem, 2017)
Hydrothermally reduced porous graphene (PGs) and polyaniline (PANI) nanofiber composites (PGs?PANI) were prepared by interfacial polymerization of aniline in the presence of reduced porous graphene (PGs) under acidic conditions. Hydrothermal reduction of graphene oxide (GO) produced graphene quantum dots (GQDs) along with porous reduced graphene (PGs). The removal of nano sized GQDs generate several round shaped edges in the graphene, which facilitated improved charge storage. In addition to preparation of porous graphene, we developed an approach to process the PGs. We envisioned preparing conjugated polymer as processing material. The capacitive behavior of PGs was characterized using cyclic voltammetry (CV) and galvanostatic charge?discharge (GCD) techniques. The specific capacitance of hydrothermally reduced GO (PGs) and PGs?PANI composites was 185 F/g and 357 F/g at 0.1 A/g in 1 M H2SO4 electrolyte. The energy density of PGs?PANI composite was obtained 49.58 W h/kg at a power density of 71.8 W/kg.

Soluble polybenzimidazoles with intrinsic porosity: synthesis, structure, properties and processability - Kumar, Vikas; Chatterjee, Shyambo; Sharma, Pragati; Chakrabarty, Suman; Avadhani, Chilukuri V.; Sivaram, Swaminathan (56Journal of Polymer Science Part A-Polymer Chemistry, 2018)
We have explored two novel comonomers, namely, 4,16-dicarboxyl[2.2]paracyclophane and 5,5,6,6-tetraamino-3,3,3,3-tetramethyl-1,1-spirobi[indane], for the synthesis of co-polybenzimidazoles (co-PBIs) with intrinsic porosity. Both these monomers possess twisted structures that can lead to awkward macromolecular shapes that cannot pack efficiently. The consequences of introducing these two monomers on the structure and properties of PBIs are reported. The random copolymers synthesized are amorphous and possess glass transition temperatures (T(g)s) greater than 400 degrees C. T-g decreases with increasing comonomer content indicating an increase in fractional free volume. The copolymers have low surface area. TEM and BET measurements show evidence of mesopore formation. The copolymers show significant carbon dioxide adsorption. Single chain molecular dynamics simulation of 24-mer repeat units shows intramolecular void spaces arising as a result of distorted polymer chain with reduced conformational mobility. These studies define a new synthetic strategy for bottoms-up synthesis of PBIs with intrinsic porosity. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1046-1057